A review of chemical and physical properties of coconut fiber in asphalt mixture - Tay, Lay Ting (2015)
This paper reviewed the chemical and physical properties of coconut fiber in asphalt mixture. Coconut fiber (CF) is natural fibers and also an agricultural waste which is abundant after extraction of juice and coconut fruit. Nowadays, CF has been studied to use in construction field to increase the strength of materials with its high tensile strength. Besides, CF also contributes to highway construction as it can improve skid resistance of asphalt pavement. CF treated with NaOH lowered the penetration value and higher the softening point of modified bitumen. Flow of bitumen also can be avoided at high mixing and compaction temperatures by adding 0.7% of fiber. In addition, the chemical and physical characteristics of CF were presented according Scanning Electron Microscopy (SEM).